End effect and near-surface buckling in a laminate composite material compres sed by a surface load. - Bystrov, V.M. (Reports of the National Academy of Sciences of Ukraine, 2019)
Using the basic relations of the three-dimensional linearized theory of stability in the framework of the piecewise- homogeneous medium model, the problem of stability of a layered composite material under compression of reinforcing layers by a surface load is solved. The case of a non-uniform subcritical state associated with an end effect in the region of application of the load is considered. A computational model is used for the boundary conditions on the lateral sides of a multilayer sample made of a composite material, which correspond to the symmetry conditions. The influence of the end effect on the attenuation of forms of a near-surface instability at diffe rent statically equivalent loads of reinforcing layers of a composite material is studied. For the numerical solution of the problem, the grid method based on the modified variation-difference approach is applied.